Investigation of regenerative nutrology of cells/molecules to the organism: a systematic review - de Oliveira, Alessandra Leal; da Silva Teixeira, Thuany; Braga, Mariana Carolina; de Lima Azevedo, Lucas Emanuel; Crepaldi, Lara Souza; Azevedo, Renata Cristina Taveira; Cordeiro, Nathalia Galindo; Carvalho, Rodrigo siqueira de; Soares, Cristiana Alvarenga Spadinger; Filho, Idiberto José Zotarelli [UNESP] (Zotarelli-Filho Scientific Works, 2024)
Introduction: In the context of tissue regeneration and nutrology, stem cells from adult tissue mediate homeostasis and regeneration of tissues and organs. These decisions are directly integrated with the body's energy balance and nutritional status. Endogenous metabolites and dietary nutrients can directly influence epigenetic enzymes. Objective: It was to carry out a systematic review of the regenerative nutrology of cells and molecules in the body. Methods: The systematic review rules of the PRISMA Platform were followed. The research was carried out from April to June 2023 in Scopus, PubMed, Science Direct, Scielo, and Google Scholar databases. The quality of the studies was based on the GRADE instrument and the risk of bias was analyzed according to the Cochrane instrument. Results and Conclusion: A total of 112 articles were found. A total of 45 articles were evaluated in full and 25 were included and developed in this systematic review study. Considering the Cochrane tool for risk of bias, the overall assessment resulted in 18 studies with a high risk of bias and 18 studies that did not meet GRADE. It was evidenced that the metabolism of stem cells was centered on the central metabolism of carbon and the balance between glycolysis versus oxidative phosphorylation in the regulation of cell destiny. Epigenetic modifications to DNA and histones, proteins that alter cellular fate, control chromatin accessibility and downstream gene expression. In addition to the connection between metabolism and epigenetic pathways, nutrients can impact cellular status by modulating signaling pathway activity. A clear example is through the mechanistic targeting of the rapamycin (mTOR) signaling pathway, and in particular the mTOR 1 complex. Nutritional supplementation accelerated the healing of skin ulcers and reduced the intensity of wound care in non-malnourished patients.
Keywords: Epigenetics; Metabolism; Nutrients; Nutrology; Tissue regeneration